THE AUTHORITY OF ANESTHESIA TECHNICIANS IN CONDUCTING ANESTHESIA PRACTICES REVIEWED IN LIGHT OF MINISTER OF HEALTH REGULATION NUMBER 18 OF 2016 REGARDING THE LICENSING AND IMPLEMENTATION OF ANESTHESIA TECHNICIAN PRACTICES (A STUDY AT MELAWI DISTRICT GENERAL HOSPITAL, WEST KALIMANTAN) - Muhammad Alief; Fitri Rafianti; Henry Aspan (Universitas Bengkulu, 2024)
This study aims to evaluate the clinical authority of anesthesia providers in relation to Health Regulation No. 18/2016 and its implementation at Melawi Regional General Hospital. Anesthesia services in Indonesia are performed by anesthesiologists and anesthetists. The government issued Minister of Health Regulation Number 18 Year 2016 on Anesthesia Practice Permits and Implementation to clarify the responsibilities of anesthesiologists in performing such medical actions. In addition, nowadays, it is highly recommended that all hospitals be accredited to measure public safety and service quality. As part of the accreditation process, all medical professionals will be required to provide evidence of proficiency by demonstrating their credentials. Therefore, the purpose of this study is to determine the clinical authority of anesthesia providers in relation to Health Regulation Number 18 Year 2016 and its implementation. Examining Health Regulation No. 18/2016 on the License to Practice and Implementation of Anesthesia, this research uses a normative juridical analytical approach. The legal review was conducted by referring to several legal materials and expert opinions. The results showed that the authority of the anesthesiologist at Melawi Regional General Hospital is in accordance with Permenkes No. 18 of 2016. The research also noted that the procedure for delegation of authority from anesthesiologist to anesthesiologist is carried out with Standard Operating Procedures that have been determined by the Melawi Regional General Hospital. Keywords: Anesthesiologist; Authority; Implementation.